معلومات وسلوكيات ممرضي مشفى الأسد الجامعي المتعلقة بتقنية غسيل الأيدي - غزال, سوسن (Latakia University Journal -Medical Sciences Series, 2016)
Compliance of health care workers to adhere to correct hand hygiene is reported to be poor in many countries although the techniques involved in hand hygiene are simple. This study yielded interesting findings regarding knowledge and behavior among a sample of 30 nurses in Al-assad university hospital in Lattakia. Nurses received a self administered paper questionnaire on knowledge and practices of hand hygiene at their workplace and were observed during their work. Only (14 %) of participants had very good knowledge about hand hygiene, with a significant difference in the level of knowledge according to the level of education as respondents with university degree were more likely to correctly identify the proper way of hand hygiene compared to those nurses who have a lower level of education. On the other hand, the overall hand hygiene compliance among nurses is 30%. Some of the key parameters associated with noncompliance have been clearly identified. Hand washing hygiene is a cheap and primary infection control procedure. Therefore, the study suggests some improvement by continuous education during shifts, seminars and posters, ensuring the availability of adequate hand washing utilities like soap, water taps, drying tissues and reducing work load to improve nurse to patient ratio.على الرغم من كون تقنية غسيل الأيدي تقنية بسيطة، سجل العديد من الأبحاث مستويات رديئة لالتزام العاملين في مجال الرعاية الصحية بتقنية غسيل الأيدي الصحيحة في العديد من البلدان. أجري هذا البحث لتقييم معلومات وسلوكيات 30 ممرض وممرضة من العاملين في مشفى الأسد الجامعي. تلقى الممرضون استبياناً شخصيا ًمتعلقاً بمعلومات ومهارات تقنية غسيل الأيدي في مكان عملهم، وتمت ملاحظتهم خلال العمل. سجل 14 % فقط من المشاركين مستوى جيد جداً فيما يتعلق بالمعلومات المتعلقة بتقنية غسيل الأيدي، مع فروقات ذات دلالة إحصائية متعلقة بمستوى التعليم حيث حدد المشاركون من خريجي الجامعة الطريقة الصحيحة لتقنية غسيل الأيدي بالمقارنة مع الدرجات العلمية الأقل. من جهة أخرى، كانت نسبة التزام الممرضين بتقنية غسيل الأيدي 30 %، مع تحديد العديد من العوامل التي تلعب دوراً في عدم الالتزام. تعتبر تقنية غسيل الأيدي تقنية بسيطة وغير مكلفة، وإجراءً أولياً من إجراءات ضبط العدوى، لذلك اقترح البحث إجراءات لتعزيز هذه التقنية عبر برامج تثقيفية خارج أوقات عمل الممرضين، وعبر سيمنارات وملصقات، بالإضافة إلى التأكيد على ضرورة توفر مستلزمات كافية للقيام بتقنية غسيل الأيدي كالصابون والماء المخصص، وورقيات التجفيف، وتقليل عدد ساعات العمل لتحسين نسبة عدد الممرضين للمرضى.